(Non-)BPS bound states and D-brane instantons - Cvetič, Mirjam; Richter, Robert; Weigand, Timo (Journal of high energy physics, 2008)
We study non-perturbative effects in four-dimensional ##IMG## [http://ej.iop.org/icons/Entities/calN.gif] Script N = 1 supersymmetric orientifold compactifications due to D-brane instantons which are not invariant under the orientifold projection. We show that they can yield superpotential contributions via a multi-instanton process at threshold. Some constituents of this configuration form bound states away from the wall of marginal stability which can decay in other regions of moduli space. A microscopic analysis reveals how contributions to the superpotential are possible when new BPS states compensate for their decay. We study this concretely for D2-brane instantons along decaying special Lagrangians in Type IIA and for D5-branes instantons carrying holomorphic bundles in Type I theory.